Abnormal DNA Patterns in Animal Mitochondria: Ethidium Bromide-Induced Breakdown of Closed Circular DNA and Conditions Leading to Oligomer Accumulation - Nass, Margit M. K. (1970)
Treatment of cultured mouse fibroblasts (L-cells) and hamster kidney cells with ethidium bromide was found to inhibit the incorporation of [(3)H]thymidine into mitochondrial closed-circular DNA, but not into nuclear DNA. The specific activity of nuclear DNA in treated cells was higher than in control cells. Treatment also led to breakdown of closed-circular mitochondrial DNA, greatly enlarged mitochondrial profiles with few or no cristae, and a higher yield of mitochondrial protein per cell. A significant increase in the content of circular DNA dimers and oligomers of mitochondria was observed after treatment of L-cells with cycloheximide and puromycin or treatment of chick fibroblasts with cycloheximide, and in hamster kidney cells transformed with polyoma virus. Little or no effects on dimer and oligomer content were found in L-cells treated with vinblastine, colcemid, rifampicin, chloramphenicol, or mengovirus, in Rous-transformed hamster cells, or in cuprizone-induced giant mitochondria of rat liver.